Effect of Curing Regime on Properties of Lightweight Concrete Containing Palm Oil Fuel Ash - Khairunisa, Muthusamy; Mohd Warid, Hussin; A. S. M., Abdul Awal (2009)
Continuous growth in the production of Malaysian palm oil has resulted in higher quantity of palm oil fuel ash disposed as waste thus causing considerable negative impact towards environment. Numerous studies have been conducted by civil engineering researchers particularly, to unearth the potential of this hazardous by-product in order to reduce amount of waste disposed at landfill as well as to produce an environmental friendly construction material. The effort has been rewarded when addition of this waste in production of ordinary concrete and high strength concrete enhance the strength and durability of the new concrete. Recently, attempt has been made to integrate this pozzolanic material as partial cement replacement in aerated concrete which has produced a new type of lightweight concrete known as palm oil fuel ash cement based aerated concrete. The early section of this paper discusses the effect of ash replacement level on the compressive strength of aerated concrete. Then, the discussion centered on laboratory test data related to compressive strength and flexural strength performance of POFA aerated concrete specimens subjected to different curing regimes namely water, wet dry cycle, natural weather and air curing. All the specimens were prepared and tested at 28 days in accordance BS 1881 and ASTM C293-79 to determine compressive strength and flexural strength respectively. Up to 30% by weight of ash replacement, no adverse effect on the strength of aerated concrete was observed. However, integration of 20% POFA as partial cement replacement gave the highest strength of any other replacement level.